Analysis of the Relationship of Multiple Intelligences and Learning Interests with Biology Learning Outcomes - Kiki Mulyani; Ramadhan Sumarmin; Yuni Ahda; Heffi Alberida; Abdul Razak (Jurnal Penelitian Pendidikan IPA, 2021)
Student learning outcomes have not reached the minimum completeness criteria. Teachers have not measured the level of Multiple Intelligences (MI) and the student's interest in learning. The learning process is still teacher-centered. This is the problem facing the world of education in the 21st century. Efforts to overcome this problem are by measuring the relationship between MI and interest in learning biology with student learning outcomes. This study aims to determine the relationship between MI as a whole and the interest in learning collectively on students' learning outcomes in Biology subjects in class X Mathematics and Natural Sciences SMA Negeri in Padang City. This research is a descriptive study that was conducted in March-April at the public high schools in Padang City for the 2020/2021 school year. The sample was taken using a purposive, random sampling technique and obtained a sample of 297 students spread across five public schools in Padang. The research instrument used the questionnaire MI, the interest in learning questionnaire, and the question HOTS. The data in this study were analyzed using multiple correlations. The results showed that there was a close relationship between MI and interest in learning with the results of studying biology class X MIPA SMAN in the city of Padang